Integration and evaluation of multiple piezo configurations for optimal health monitoring of reinforced concrete structures. (November 2017) - Kaur, Naveet; Li, Lingfang; Bhalla, Suresh; Xia, Yong; Ni, Pinghe; Adhikari, Sailesh
Since the last two decades, the electro-mechanical impedance technique has undergone extensive theoretical and experimental transformations coupled with the evolution of newer practical adaptations and variants. Notable among these are the metal wire–based variant, the dual piezo configuration and the embedded configuration, over and above the conventional surface-bonded configuration. Although there is a plethora of electro-mechanical impedance–related research devoted to metallic structures, only a limited number of studies are available for reinforced concrete structures, which are characterized by more complex behaviour and pose multiple problems for the electro-mechanical impedance sensors such as small range and high damping due to heterogeneous constitution. This article presents, for the first time, a comprehensive comparative study covering four different variants, namely, the surface-bonded single piezo configuration, the embedded single piezo configuration and the metal wire single piezo configuration in electro-mechanical impedance technique for structural health monitoring of a real-life-sized reinforced concrete beam subjected to destructive testing. The article also proposes a modified and more practical version of the dual piezo configuration called the modified dual piezo configuration, employing concrete vibration sensors. It is found that the modified dual piezo configuration is the most expedient among all variants in capturing the damage with respect to the first occurrence of cracks and the final warning of ultimate failure. Metal wire single piezo configuration is good in detecting the first level of damage; however, its efficiency ceases thereafter when crack size increases. It can be considered as an alternative to surface-bonded single piezo configuration in the scenarios where the damage level is incipient. The sensitivity of the modified dual piezo configuration increases with increasing number of actuators connected in parallel due to an increase in the output current. Also, contrary to the surface-bonded single piezo configuration, the susceptance signature of the modified dual piezo configuration is equally sensitive to damage due to the absence of capacitance part in its admittance signature. Hence, its susceptance can also be used for damage severity measurement for incipient damage level in reinforced concrete structures. The surface-bonded single piezo configuration is found to be best in quantifying damage severity in terms of the equivalent stiffness parameter. Embedded single piezo configuration and metal wire single piezo configuration, on the other hand, correlate well with the global dynamic stiffness of the structure. Overall, the proposed integration enables an early detection of damage, its propagation and improved severity measurement for reinforced concrete structures, thus contributing to new application protocols.